The Effect Of Hazardous Geologic Structures On Gateroad Stability - Frank E. Chase (International Conference on Ground Control in Mining, 1990)
Geologic structures have been responsible for numerous underground accidents and fatalities, and are a constant-source of down time. During - longwall mining, ground control problems associated with geologic anomalies are aggravated by the abutment pressures which develop as the panel is retreated. Therefore, it is imperative that these structures be recognized and properly supported in head- and tailgates. Fractures, faults, clay veins, igneous dikes, and ancient stream channels (paleochannels) disrupt the lateral continuity of the mine roof and can cause falls in gateroads. Horsebacks and kettle bottoms are also hazardous because abutment pressures tend to "pop out' these structures into the gateroads. This Bureau of Mines investigation describes the physical characteristics associated with hazardous geologic structures, identifies the coal fields where-they have been observed, and, where possible, suggests support strategies and other mine plan modifications to help minimize their effect.